2012
DOI: 10.1371/journal.pone.0041395
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Flow along Venous Adventitia in Rabbits: Is It a Potential Drainage System Complementary to Vascular Circulations?

Abstract: BackgroundOur previous research and other studies with radiotracers showed evidence of a centripetal drainage pathway, separate from blood or lymphatic vessels, that can be visualized when a small amount of low molecular weight tracer is injected subcutaneously into a given region on skin of humans. In order to further characterize this interesting biological phenomenon, animal experiments are designed to elucidate histological and physiologic characteristics of these visualized pathways.MethodsMultiple tracer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
67
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(76 citation statements)
references
References 34 publications
(41 reference statements)
8
67
0
1
Order By: Relevance
“…In summary, the behaviours of the imaging tracers strongly suggested that specific anatomical structures located within the subcutaneous tissues or the partial walls of some veins are unique transport pathways that originate from the subcutis of anatomical extremities and possibly connect with certain ''internal organs'', as was previously described in rabbits [6]. We believe that the challenge of developing more techniques for the detection of longitudinal non-vascular transport pathways within the extremities, various organs in splanchnocoele and even within the Centrifugal and centripetal transport of the fluorescein injected into LU9 (a-c) and (d-f).…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…In summary, the behaviours of the imaging tracers strongly suggested that specific anatomical structures located within the subcutaneous tissues or the partial walls of some veins are unique transport pathways that originate from the subcutis of anatomical extremities and possibly connect with certain ''internal organs'', as was previously described in rabbits [6]. We believe that the challenge of developing more techniques for the detection of longitudinal non-vascular transport pathways within the extremities, various organs in splanchnocoele and even within the Centrifugal and centripetal transport of the fluorescein injected into LU9 (a-c) and (d-f).…”
Section: Discussionsupporting
confidence: 58%
“…To the best of our knowledge, neither anatomical nor histological knowledge can explain this phenomenon in humans. Notably, we have reported that the perivenous loose connective tissues (including the venous adventitia) of vascular trees can transport interstitial fluid from extremities into pericardial cavities in rabbits, which might offer valuable insight into the precise histological structures of the enhanced ''partial walls of veins'' in humans [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, the peripheral fluorescent ISF was found in the walls of segmental small intestines and right pulmonary veins as well, which indicated that there was probably more than one centre of IDT driving powers in physiological conditions. The measured speed of venous adventitial ISF flow was around 0.2‐2 cm/s in the rabbit . By Doppler technique, the measured speed of femoral arterial blood flow in the rabbit was around 5‐50 cm/s and the femoral venous blood flow was around 6‐7 cm/s .…”
Section: Our Experimental Discoveries About the Systemic Isf Transportmentioning
confidence: 91%